PENGARUH PEMBERIAN EKSTRAK BUAH PIDADA MERAH (Sonneratia caseolaris) TERHADAP PERBAIKAN HISTOPATOLOGI PANKREAS TIKUS GALUR WISTAR DIABETIK - Candra Achmad Abdillah, - (2023)
Diabetes Mellitus (DM) has become a global problem with a prevalence that continues to increase every year. Diabetes Mellitus increases ROS (Reactive Oxygen Species) and inflammation in individuals, which can damage organs. Red Pidada fruit contains flavonoids, saponins, and tannins that are beneficial as anti-hyperglycemic, antioxidant, and anti-inflammatory agents. This study aims to determine the effect of red Pidada fruit extract on the pancreatic histopathology of Wistar rats induced with alloxan and high-fat diet. The study is experimental in nature, using a randomized post-control group design, with male Wistar rat samples (Rattus norvegicus) aged 2-3 months and weighing 150-200 grams. The rats were divided into 6 groups. Group 1 was given a standard diet and aquadest. Groups 2, 3, 4, 5, and 6 were given a high-fat diet for 28 days and then induced with 125 mg/kgBW of alloxan intraperitoneally. Group 3 was given glibenclamide 0.09 mg/kgBW/day. Groups 4, 5, and 6 were given red Pidada fruit extract at doses of 200, 400, and 800 mg/kgBW/day, respectively. The treatment was administered for 14 days. Mann-Whitney test showed that red Pidada fruit extract at a dose of 800 mg/kgBW/day had the best effect on the histopathological improvement of the pancreas, which was almost the same as the administration of glibenclamide (p value 0.134).